Reimagining Urban Nature Literary Imaginaries for Posthuman Cities - Bayes, Chantelle (Liverpool University Press, 2023)
Reimagining Urban Nature questions some of the underlying imaginaries which have for so long allowed us humans to develop technologically at great cost to the more-than-human world and ourselves. In urban places, cultural and more-than-human entities are in frequent contact; however, the non-human is often seen as expendable in these human-centric places. While much important work has been done on improving care for the more rural and wild areas of the globe, to really address environmental damage we must work towards reimagining the city. These are places where the majority of people live and work, and where the majority of decisions are made about the care and protection of many environments within and beyond the city. This book contributes to the still under-developed field of urban ecocriticism by adding a posthumanist perspective, as well as expanding current discussions within urban studies and environmental activism that seek to shift political and cultural imaginaries of urban nature. Importantly, this investigation is grounded in the Australian (and more broadly, the Australasian) context to allow for the analysis of a more diverse set of voices, texts and ecologies in an area still dominated by the northern hemisphere and the Global North.